2019
DOI: 10.1515/cdbme-2019-0073
|View full text |Cite
|
Sign up to set email alerts
|

Catheter pose-dependent virtual angioscopy images visualized on augmented reality glasses

Abstract: Fluoroscopy and digital subtraction angiography provide guidance in endovascular aortic repair (EVAR) but introduce radiation exposure and require the administration of contrast agent. To overcome these disadvantages, previous studies proposed to display the pose of an electromagnetically (EM) tracked catheter tip within a three-dimensional virtual aorta on augmented reality (AR) glasses. For further guidance, we propose to create virtual angioscopy images based on the catheter tip pose within the aorta and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The EM data is sent from the EM tracking system to the NavEvar application via the open-source software PLUS Toolkit (https://plustoolkit.github. io) [2]. The virtual camera produces images of 512 × 512 pixels and the field of view (in degrees) can be adjusted.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The EM data is sent from the EM tracking system to the NavEvar application via the open-source software PLUS Toolkit (https://plustoolkit.github. io) [2]. The virtual camera produces images of 512 × 512 pixels and the field of view (in degrees) can be adjusted.…”
Section: Methodsmentioning
confidence: 99%
“…To reduce EVAR limitations, a recent study reported the integration of a multicore fiber with fiber Bragg gratings and two electromagnetic (EM) sensors into a stent graft system to locate the shape of the endovascular tool with respect to the patient's anatomy (in that case, a patient-specific aortic phantom) [1]. In addition, virtual angioscopy images were rendered based on the pose (position and orientation) of an EM-tracked catheter tip [2]. These images of the vessel lumen were visualised on a virtual 2D canvas superimposed on the real scenario with the augmented reality glasses Microsoft HoloLens (first generation).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations